Fintech Based Investment Analysis (Peer to Peer Lending) in Sharia Economic Law and Positive Law - Santoso, Rudi; Zaharah, Rita; Fikri, Arif; Alia Rahma, Fuji (KnE Social Sciences, 2024)
The development of digital technology today creates updates in all aspects of life, including investment. Investment is not something that is prohibited in Islam, but in practice, it must pay attention to Sharia principles. With the emergence of financial technology (Fintech)-based investment systems in various platforms, one of which is peer to peer (P2P) lending balanced with high levels of investment among millennials. In this case, Indonesian society, which is predominantly Muslim, must be careful in analyzing and making choices in investing, whether it is following the Shari’a and how the law regulates it. This research includes juridical-normative law research, to find out the review of Islamic law and positive law on fintech P2P lending and a conceptual approach to find out the concept of fintech P2P lending. The results of the study found that investment through the P2P lending platform is permissible in Islam with terms and conditions that are in accordance with Shari’ah principles. The contracts that can be used in P2P lending are al-bai’, ijarah, mudharabah, musyarakah, wakalah bi al ujrah, and qardh contracts. Every P2P Lending provider must obtain a permit from the Financial Services Authority (OJK) to run the entire lending system (POJK No. 77/POJK.01/2016) as well as follow the provisions of the DSN MUI Fatwa Number 117 of 2018. In positive law, it is regulated in the Civil Code, POJK Number 10 of 2022 and Bank Indonesia Regulation Number 19/12/PBI/2017. Keywords: investment, peer to peer lending, law